Clinical application of pedicled thoracoacromial artery perforator flaps for tracheal reconstruction - Deng, Di (BMC Surg, 2020)
BACKGROUND: Large or complex trachea defects often require some tissue to reconstruct, various flaps have been reported for reconstructing this defect. However, pedicled thoracoacromial artery perforator flap have not been reported in tracheal reconstruction. Therefore, this study is to assess the efficacy and clinical application of pedicled thoracoacromial artery perforator flaps for tracheal reconstruction. METHODS: Eight patients who underwent tracheal reconstructions with pedicled TAAP flaps between December 2017 and October 2019 were retrospectively reviewed. RESULTS: All of the pedicled TAAP flaps in our study survived. The flap size ranged from 2 cm × 5 cm to 4 cm × 10 cm, and the size of each island of one double-island flap was 2 cm × 2.5 cm. The mean thickness was 0.6 cm, and the pedicle length varied between 6 and 9 cm (mean 7.9 cm). The mean time of flap harvest was 17 min. The mean age of the patients was 62.4 years and five elderly patients had comorbidities, such as diabetes, hypertension and asthma. One patient received a double-island flap for tracheal and esophageal reconstruction, and the other patient received simple tracheal reconstruction. One patient died due to cancer metastasis. Six patients obtained functional recovery of breathing, except one patients who did not experience closure of the tracheostomy opening due to uncompleted I131 treatment. CONCLUSION: Pedicled TAAP flaps provide a short harvesting time, thin thickness and stable blood supply, and they do not require microsurgical skills. This flap is a good choice for the reconstruction of tracheal defects, especially in the aged or patients with comorbidities who are not able to tolerate prolonged surgery.